Answer:
x=1
y=-4
Step-by-step explanation:
4x+y=0 -> y= -4x
2(-4x)+x=-7
-8x+ x=-7
-7x=-7
x=-7/-7=1
y=-4 . 1 = -4
Let x represent amount invested in the higher-yielding account.
We have been given that a man puts twice as much in the lower-yielding account because it is less risky. So amount invested in the lower-yielding account would be .
We are also told that his annual interest is $6600 dollars. We know that annual interest for one year will be principal amount times interest rate.
, where,
I = Amount of interest,
P = Principal amount,
r = Annual interest rate in decimal form,
t = Time in years.
We are told that interest rates are 6% and 10%.
Amount of interest earned from lower-yielding account: .
Amount of interest earned from higher-yielding account: .
Let us solve for x.
Therefore, the man invested $30,000 at 10%.
Amount invested in the lower-yielding account would be .
Therefore, the man invested $60,000 at 6%.
Y = -x²
y = -7x²
<u>y = 2/3x²</u>
<u>3y</u> = <u>-7 1/3x²
</u> 3 3
y = -2 4/9x